2003
DOI: 10.3917/rfs.445.0029
|View full text |Cite
|
Sign up to set email alerts
|

Crime and Socio-Economic Context

Abstract: Thinking in France on relations between crime rate trend and evolution of socioeconomic context over time is underdeveloped. Recent studies in the United Kingdom suggest that the business cycle influences fluctuations in both property offenses and violent crime. Whereas pre-1970 research in the United States only rarely pointed up a direct link between crime rate and unemployment, post-1970 American studies are dominated by demonstrations of a direct correlation between the two. In this article, analysis of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…The variable of prices has a positive and significant influence on homicide rates, indicating that an increase in prices generates a higher rate of violence. Lagrange (2003) showed that an increase in opportunities to commit crimes exists when a consumer price trend is increased, which is consistent with our results. In the Colombian case, Dube and Vargas (2008) demonstrated that price shocks affect crime and violence in different ways depending on the factor intensity of the commodity; i.e., the price of natural resources, which are capital intensive, is positively related to violence and crime.…”
Section: Empirical Findings and Econometric Resultssupporting
confidence: 93%
“…The variable of prices has a positive and significant influence on homicide rates, indicating that an increase in prices generates a higher rate of violence. Lagrange (2003) showed that an increase in opportunities to commit crimes exists when a consumer price trend is increased, which is consistent with our results. In the Colombian case, Dube and Vargas (2008) demonstrated that price shocks affect crime and violence in different ways depending on the factor intensity of the commodity; i.e., the price of natural resources, which are capital intensive, is positively related to violence and crime.…”
Section: Empirical Findings and Econometric Resultssupporting
confidence: 93%
“…Our study also relates to the literature on the effects of the business cycle on crime, since the phylloxera crisis constituted a strong negative shock to the French economy. Consistent with our findings, this literature finds that trends in property crimes in the USA and France are countercyclical (Cook and Zarkin, ; Lagrange, ).…”
supporting
confidence: 91%